2012
DOI: 10.1038/ejhg.2012.130
|View full text |Cite
|
Sign up to set email alerts
|

To tell or not to tell? A systematic review of ethical reflections on incidental findings arising in genetics contexts

Abstract: Any test that produces visual images or digital or genetic sequences will tend to produce incidental findings because more will be visible than what was originally sought. We conducted a systematic review of the ethical reasons presented in the literature for and against the disclosure of incidental findings arising in clinical and research genetics contexts. A search of electronic databases resulted in 13 articles included for systematic review. Articles presented reasons for and against disclosure, and reaso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
126
0
1

Year Published

2012
2012
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(132 citation statements)
references
References 37 publications
5
126
0
1
Order By: Relevance
“…17 Most of these arguments are based on theoretical considerations and were not derived from studies of research participants. A systematic review on the ethical reflections on IFs was also conducted by Christenhusz et al 18 Considerations of WES in minors and the suggestion that parents could decide to learn about the risk for adult-onset diseases in their children have been raised as risks to an open future. The psychological impact for children and parents is unknown but could be considerable.…”
Section: Discussionmentioning
confidence: 99%
“…17 Most of these arguments are based on theoretical considerations and were not derived from studies of research participants. A systematic review on the ethical reflections on IFs was also conducted by Christenhusz et al 18 Considerations of WES in minors and the suggestion that parents could decide to learn about the risk for adult-onset diseases in their children have been raised as risks to an open future. The psychological impact for children and parents is unknown but could be considerable.…”
Section: Discussionmentioning
confidence: 99%
“…Efforts to bring the investigator's perspective into 320 the debate regarding the return of research results are growing (1)(2)(3)(4)(5). Collateral to this has been the growing debate about the duty of investigators to return incidental findings (IFs) during whole-genome sequencing (WGS) based projects, which are becoming more commonplace (3,5,6). IFs are defined as discoveries concerning an individual research participant that are found during the course of research but are beyond the scope and purpose of the study (7).…”
mentioning
confidence: 99%
“…10 A recent review on incidental findings in genetic testing also underlines the problem of unclear definitions and the problematic terminology for this type of results. 16 We suggest using a uniform name for disease-causing array findings, namely, pathogenic, which means that 'the CNV is documented as clinically significant in multiple peer-reviewed publications, even if penetrance and expressivity of the CNV are known to be variable' . 1 Based on our experience we recommend using three subcategories of pathogenic array findings: causative array findings, unexpected diagnoses and susceptibility loci for neurodevelopmental disorders (Table 1).…”
mentioning
confidence: 99%